SUPERVISI AKADEMIK KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU KEJURUAN - Tjipto Djuhartono; Ulfiah Ulfiah; Hanafiah Hanafiah; Deti Rostini (Universitas Indraprasta PGRI, 2021)
This study aims to determine the academic supervision of Principals in Vocational High Schools in improving the performance of vocational teachers, specifically this study wants to find out the problems and efforts of the academic division in improving teacher performance in terms of planning, organizing, implementing, evaluating, following up, and problems and solutions. The method used in this research is a qualitative approach with a case study method of data collection and analysis techniques, namely interviews, observation and documentation study with trianguals. As a source of research data refers to the principal, teachers, students, education staff, people parents and supervisor of the Vocational High School of Bekasi city. The results of the study are a mapping of the performance of vocational teachers from the implementation of the school principal's academic supervision program, which has a clear direction towards positive change for all vocational teacher activities in learning that have a simultaneous impact on teacher performance and improvement of the quality of vocational high school education in Bekasi city. Thus the researcher recommends that the principal as a leader in the school can continue to develop teacher competencies given the rapid changes in science and technology followed by the labor market in the business and industrial world. And the output is the concept of the principal's academic supervision model for vocational teachers.